An act for regulating marriage and for the orderly solemnization thereof ([publisher not identified], 1821)
1821 House act regulating marriage and for the orderly solemnization thereof. Included were banned relationships to marriage, requirement of marriage banns and the authorization of the justice of the peace and ordained ministers to perform marriage ceremonies, and other related matters.